Examination of mechanisms underlying enhanced memory performance in action video game players: a pilot study - Li, Xianchun; Cheng, Xiaojun; Li, Jiaying; Pan, Yafeng; Hu, Yi; Ku, Yixuan (Frontiers in Psychology, 2015)
Previous studies have shown enhanced memory performance resulting from extensive action video game playing. The mechanisms underlying the cognitive benefit were investigated in the current study. We presented two types of retro-cues, with variable intervals to memory array (Task 1) or test array (Task 2), during the retention interval in a change detection task. In Task 1, action video game players (AVGPs) demonstrated steady performance while non-action video game players (NVGPs) showed decreased performance as cues occurred later, indicating their performance difference increased as the cue-to-memory-array intervals became longer. In Task 2, both participant groups increased their performance at similar rates as cues presented later, implying the performance difference in two groups were irrespective of the test-array-to-cue intervals. These findings suggested that memory benefit from game plays is not attributable to the higher ability of overcoming interference from the following stimuli. Implications for the future studies were discussed.